Knowledge, attitude and practice of dental students and practitioners during the early days of COVID‐19 pandemic in India: A cross‐sectional study. Issue 11 (21st September 2021) - Rao, Lakshmi Nidhi; Shetty, Aditya; Latha Senthilkumar, Priyanka; Shetty, Kailkere Shreya; Shetty, Bhavya; Natarajan, Srikant; Rao, Prasanna Kumar; Baliga, Manjeshwar Shrinath
Abstract: Aim: The novel coronavirus disease‐2019 (COVID‐19) is a major health problem and has affected innumerable people around the world. The current online‐based study was conducted to assess the knowledge, attitude and practice (KAP) of dental students and professionals during the early days of lockdown in India from 2 April to 1 May 2020. Methodology: An online‐based cross‐sectional study was undertaken through WhatsApp messenger and e‐mail groups among dental students and professionals. The KAP on COVID‐19 was ascertained using an investigator designed and validated questionnaire. The results were stratified based on student vs professionals. The data were expressed as frequency and percentage analysed using the chi‐square/Fishers exact test using IBM version 17. A probability value of <.05 was considered significant. Results: A total of 287 complete responses from the dental students and professionals were received. The results indicated that the knowledge of both dental students and professionals were good and that the attitude and practice were in accordance with good clinical practice. No significant differences were found within the domains of KAP scores among the dental students and practitioners indicating that the study participants were abreast with the recent advances. Conclusion: The results of this study conducted during the early stage of the lockdown indicated that the dental students and professionals who had filled the questionnaire had very good knowledge of coronavirus and COVID‐19. Clinical implications: The results of the study indicate that the volunteers had good knowledge, attitude and self‐care practice, which are necessary in preventing the spread of COVID‐19. It is anticipated that detailed hands‐on training in practical aspects of good clinical practice with protective gears will help students and professionals perform the necessary dental procedures in accordance with the guidelines set by Centers for Disease Control and Prevention and World Health Organization.